Centralized allocation of decision rights and enterprise transformation and upgrading: Based on human capital level and capital allocation efficiency - Qingliu Tang; Hongfeng Sun (PLoS ONE, 2025)
Under the pressure of transformation and upgrading caused by complex environments at home and abroad, it is significant to explore how the centralized allocation of decision rights affects enterprise transformation and upgrading. Employing the data of Chinese A-share listed companies from 2010 to 2021, we demonstrate that the centralized allocation of decision rights significantly promotes enterprise transformation and upgrading. Further analysis indicates that enhanced human capital level and capital allocation efficiency are potential mechanisms through which centralized allocation of decision rights affects enterprise transformation and upgrading. Moreover, we document that the above positive correlation is more evident for groups with a high matching between cash flow rights and control rights, groups with strong supervision of major shareholders, and groups with a strong willingness of subsidiaries to cooperate. Collectively, these findings confirm the governance advantages of the centralized allocation of decision rights and provide important implications for enterprises’ transformation and upgrading in emerging market countries.